The role of gut microbiota in modulating immune responses in chronic liver disease: a systematic review and meta-analysis - Gadour, Eyad; Shrwani, Khalid Jebril; Hassan, Zeinab; Miutescu, Bogdan (Frontiers in Immunology, 2025)
IntroductionThe gut microbiota plays a crucial role in regulating immune responses and maintaining a balance within the gut-liver axis. In patients with chronic liver disease (CLD), alterations in gut microbiota have been linked to disease progression and impaired immune function. This study aimed to evaluate the impact of gut-modulating therapies on the immune responses of patients with CLD.MethodTwo independent authors conducted a comprehensive literature search using complementary strategies to identify relevant articles published until March 2025. Review Manager Software (RevMan 5.4) was used for data analysis, and the results were presented using forest plots. ResultsOf the 373 identified studies, 16 were included in the analysis. The findings revealed that gut microbiota-modulating therapies significantly reduced tumor necrosis factor-α (TNF-α) levels compared to control interventions (standardized mean difference [SMD], -0.60; 95% confidence interval [CI] [-0.93, -0.23] p = 0.001), with similar results observed at the 6-month follow-up (SMD -1.3; 95% CI [-2.1, -0.4] p = 0.004). Interleukin-6 (IL-6) levels showed no significant change between the groups (SMD, -0.67; 95% CI [-1.5, 0.12) p = 0.09). C-reactive protein (CRP) levels were significantly reduced by gut-modulating therapies (SMD -1.057; 95% CI [-1.493, -0.621] p = 0.0005), with consistent results at 1- and 6-month follow-up. Changes in interferon-gamma (IFN-γ) and IL-18 levels and cellular immunity were also assessed. ConclusionThis study highlights the importance of gut microbiota in modulating immune responses in patients with CLD and demonstrates the effectiveness of long-term gut-modulating therapies in reducing inflammatory markers. While CRP and TNF-α levels decreased, changes in IL-6 levels were inconsistent, warranting further research to elucidate the impact of gut microbiota-modulating therapies on this biomarker.